Dual nanomechanics in anisotropic porous covalent organic framework janus-type thin films - Mohata, Shibani; Dey, Kaushik; Bhunia, Surojit; Thomas, Neethu; Gowd, E. Bhoje; Ajithkumar, Thalasseril G.; Reddy, C. Malla; Banerjee, Rahul (Journal of the American Chemical Society, 2022)
Empowered by crystalline ordered structures and homogeneous fabrication techniques, covalent organic frameworks (COFs) have been realized with uniform morphologies and isotropic properties. However, such homogeneity often hinders various surface-dependent properties observed in asymmetric nanostructures. The challenge remains to induce heterogeneity in COFs by creating an asymmetric superstructure such as a Janus thin film. In this regard, we propose a versatile yet straightforward interfacial layer-grafting strategy to fabricate free-standing Janus-type COF-graphene thin films. Herein, two-dimensional graphene sheets were utilized as the suitable grafter due to the possibility of noncovalent interactions between the layers. The versatility of the approach was demonstrated by fabricating two distinct Janus-type films, with the COF surface interwoven with nanofibers and nanospheres. The Janus-type films showcase opposing surface morphologies originating from graphene sheets and COF nanofibers or nanospheres, preserving the porosity (552-600 m(2) g(-1)). The unique surface chemistries of the constituent layers further endow the films with orthogonal mechanical properties, as confirmed by the nanoindentation technique. Interestingly, the graphene sheets favor the Janus-type assembly of COF nanofibers over the nanospheres. This is reflected in the better nanomechanical properties of COFfiber-graphene films (E-gra(phene) = 300-1200 MPa; E-COF( )= 15-60 MPa) compared to the COFsphere-graphene films (E-gra(phe)ne = 11-14 MPa; E-CO(F )= 2-5 MPa). These results indicate a direct relationship between the mechanical properties and homo/heterogeneity of Janus-type COF films.

Viscoelastic covalent organic nanotube fabric via macroscopic entanglement - Koner, Kalipada; Das, Susobhan; Mohata, Shibani; Duong, Nghia Tuan; Nishiyama, Yusuke; Kandambeth, Sharath; Karak, Suvendu; Reddy, C. Malla; Banerjee, Rahul (Journal of the American Chemical Society, 2022)
Covalent organic nanotubes (CONTs) are one-dimensional porous frameworks constructed from organic building blocks via dynamic covalent chemistry. CONTs are synthesized as insoluble powder that restricts their potential applications. The judicious selection of 2,2'-bipyridine-5,5'-dicarbaldehyde and tetraaminotriptycene as building blocks for TAT-BPy CONTs has led to constructing flexible yet robust and self-standing fabric up to 3 mu m thickness. The TAT-BPy CONTs and TAT-BPy CONT fabric have been characterized by solid-state one-dimensional (1D) C-13 CP-MAS, two-dimensional (2D) C-13-H-1 correlation NMR, 2D H-1-H-1 DQ-SQ NMR, and 2D N-14-H-1 correlation NMR spectroscopy. The mechanism of fabric formation has been established by using high-resolution transmission electron microscopy and scanning electron microscopy techniques. The as-synthesized viscoelastic TAT-BPy CONT fabric exhibits high mechanical strength with a reduced modulus (E-r) of 8 (+/- 3) GPa and hardness (H) of 0.6 (+/- 0.3) GPa. Interestingly, the viscoelastic fabric shows time-dependent elastic depth recovery up to 50-70%.

Morphology tuning via linker modulation: metal-free covalent organic nanostructures with exceptional chemical stability for electrocatalytic water splitting - Karak, Shayan; Koner, Kalipada; Karmakar, Arun; Mohata, Shibani; Nishiyama, Yusuke; Duong, Nghia Tuan; Thomas, Neethu; Ajithkumar, Thalasseril Govindankuttykaimal; Hossain, Munshi Sahid; Bandyopadhyay, Subhajit; Kundu, Subrata; Banerjee, Rahul (Advanced Materials, 2024)
The development of synthetic routes for the formation of robust porous organic polymers (POPs) with well-defined nanoscale morphology is fundamentally significant for their practical applications. The thermodynamic characteristics that arise from reversible covalent bonding impart intrinsic chemical instability in the polymers, thereby impeding their overall potential. Herein, a unique strategy is reported to overcome the stability issue by designing robust imidazole-linked POPs via tandem reversible/irreversible bond formation. Incorporating inherent rigidity into the secondary building units leads to robust microporous polymeric nanostructures with hollow-spherical morphologies. An in-depth analysis by extensive solid-state NMR (1D and 2D) study on H-1, C-13, and N-14 nuclei elucidates the bonding and reveals the high purity of the newly designed imidazole-based POPs. The nitrogen-rich polymeric nanostructures are further used as metal-free electrocatalysts for water splitting. In particular, the rigid POPs show excellent catalytic activity toward the oxygen evolution reaction (OER) with long-term durability. Among them, the most efficient OER electrocatalyst (TAT-TFBE) requires 314 mV of overpotential to drive 10 mA cm(-2) current density, demonstrating its superiority over state-of-the-art catalysts (RuO2 and IrO2).
Keywords: bi-functional electrocatalysts; chemically robust; hollow-spherical morphologies; imidazole-linked; inherent rigidity; metal-free; water splitting